Luspatercept for the treatment of anaemia in patients with lower-risk myelodysplastic syndromes (PACE-MDS): a multicentre, open-label phase 2 dose-finding study with long-term extension study. Issue 10 (October 2017) - Platzbecker, Uwe; Germing, Ulrich; Götze, Katharina S; Kiewe, Philipp; Mayer, Karin; Chromik, Jörg; Radsak, Markus; Wolff, Thomas; Zhang, Xiaosha; Laadem, Abderrahmane; Sherman, Matthew L; Attie, Kenneth M; et al.
Summary: Background: Myelodysplastic syndromes are characterised by ineffective erythropoiesis. Luspatercept (ACE-536) is a novel fusion protein that blocks transforming growth factor beta (TGF β) superfamily inhibitors of erythropoiesis, giving rise to a promising new investigative therapy. We aimed to assess the safety and efficacy of luspatercept in patients with anaemia due to lower-risk myelodysplastic syndromes. Methods: In this phase 2, multicentre, open-label, dose-finding study (PACE-MDS), with long-term extension, eligible patients were aged 18 years or older, had International Prognostic Scoring System-defined low or intermediate 1 risk myelodysplastic syndromes or non-proliferative chronic myelomonocytic leukaemia (white blood cell count <13 000/μL), and had anaemia with or without red blood cell transfusion support. Enrolled patients were classified as having low transfusion burden, defined as requiring less than 4 red blood cell units in the 8 weeks before treatment (and baseline haemoglobin <10 g/dL), or high transfusion burden, defined as requiring 4 or more red blood cell units in the 8 weeks before treatment. Patients received luspatercept subcutaneously once every 21 days at dose concentrations ranging from 0·125 mg/kg to 1·75 mg/kg bodyweight for five doses (over a maximum of 12 weeks). Patients in the expansion cohort were treated with 1·0 mg/kg luspatercept; dose titration up to 1·75 mg/kg was allowed, and patients could be treated with luspatercept for a maximum of 5 years. Patients in the base study were assessed for response and safety after 12 weeks in order to be considered for enrolment into the extension study. The primary endpoint was the proportion of patients achieving modified International Working Group-defined haematological improvement–erythroid (HI-E), defined as a haemoglobin concentration increase of 1·5 g/dL or higher from baseline for 14 days or longer in low transfusion burden patients, and a reduction in red blood cell transfusion of 4 or more red blood cell units or a 50% or higher reduction in red blood cell units over 8 weeks versus pre-treatment transfusion burden in high transfusion burden patients. Patient data were subcategorised by: luspatercept dose concentrations (0·125–0·5 mg/kg vs 0·75–1·75 mg/kg); pre-study transfusion burden (high transfusion burden vs low transfusion burden, defined as ≥4 vs <4 red blood cell units per 8 weeks); pre-study serum erythropoietin concentration (<200 IU/L, 200–500 IU/L, and >500 IU/L); presence of 15% or more ring sideroblasts; and presence of SF3B1 mutations. Efficacy analyses were carried out on the efficacy evaluable and intention-to-treat populations. This trial is currently ongoing. This study is registered withClinicalTrials.gov, numbersNCT01749514 andNCT02268383 . Findings: Between Jan 21, 2013, and Feb 12, 2015, 58 patients with myelodysplastic syndromes were enrolled in the 12 week base study at nine treatment centres in Germany; 27 patients were enrolled in the dose-escalation cohorts (0·125–1·75 mg/kg) and 31 patients in the expansion cohort (1·0–1·75 mg/kg). 32 (63% [95% CI 48–76]) of 51 patients receiving higher dose luspatercept concentrations (0·75–1·75 mg/kg) achieved HI-E versus two (22% [95% CI 3–60]) of nine receiving lower dose concentrations (0·125–0·5 mg/kg). Three treatment-related grade 3 adverse events occurred in one patient each: myalgia (one [2%]), increased blast cell count (one [2%]), and general physical health deterioration (one [2%]). Two of these treatment-related grade 3 adverse events were reversible serious grade 3 adverse events: one patient (2%) had myalgia and one patient (2%) had general physical health deterioration. Interpretation: Luspatercept was well tolerated and effective for the treatment of anaemia in lower-risk myelodysplastic syndromes and so could therefore provide a novel therapeutic approach for the treatment of anaemia associated with lower-risk myelodysplastic syndromes; further studies are ongoing. Funding: Acceleron Pharma.